Respostas
respondido por:
0
- 2x + y = 18
x + y = 30 x(-1)
-2x + y = 18
-x - y = - 30
-3x = - 12 x( -1)
3x = 12
x = 12/3
x = 4
y = 2 . 4 + 18
y = 8 + 18
y = 26
x + y = 30 x(-1)
-2x + y = 18
-x - y = - 30
-3x = - 12 x( -1)
3x = 12
x = 12/3
x = 4
y = 2 . 4 + 18
y = 8 + 18
y = 26
respondido por:
0
y=2x+18
y=-x+30
(y) = (-x+30)
2x+18 = -x+30
2x+x = 30-18
3x = 12
x = 12/3
x = 4
substituir x na equaçao:
y = -(4) +30
y = 30 - 4
y = 26
y=-x+30
(y) = (-x+30)
2x+18 = -x+30
2x+x = 30-18
3x = 12
x = 12/3
x = 4
substituir x na equaçao:
y = -(4) +30
y = 30 - 4
y = 26
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás